Hubungan Persepsi Keterampilan Mengajar Guru dengan Motivasi Belajar Siswa Akselerasi di Sekolah Menengah Atas Al-Azhar Medan - Damanik, Suri Handayani; Anggaraeni, Filia Dian (Universitas Medan Area, 2018)
The purpose of this research is to know the correlation between perception of teacher teaching skills and students motivation to learn Sociology at acceleration class of SMA Swasta Al-Azhar Medan. Method used in this research is descriptive correlation and the population is all of acceleration class students at SMA Swasta Al-Azhar Medan in 2009/2010, that is 34 students. Sampling method which is used in this research is total sampling (all of population member used as sample). Data collected by using the questionnaire with Likert Scale. The reliability of each instruments are 0,941 for perception of teacher teaching skills, and 0,864 for students motivation to learn. Method of data analyze is Pearson correlation test (Pearson Product Moment).The result of this research indicate that there is a significant correlation between perception of teacher teaching skills and students motivation to learn (r = 0,352). The conclusion indicate that the perception of teacher teaching skills relate to students motivation to learn Sociology at acceleration class of SMA Swasta Al-Azhar Medan.